AN EMPIRICAL ANALYSIS OF AUDIT DELAY IN TURKEY - TüREL, Ash; TUNCAY2, Ferhan Emir (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 18 (2016): Annales Universitatis Apulensis Series Oeconomica, 2016)
The main purpose of this study is to examine the factors that affect delays in the signing of audit reports in Turkey. The audit delay is measured as a function of the number of days that elapse from the accounting period until the date when the audit report is signed. This study utilizes a sample of 508 firms listed on the Borsa Istanbul in 2013. The findings indicate that the companies that report net income, that have standard audit opinion release their audited financial statements earlier. Variables such as auditor firm and leverage show no significant relationship with audit delay.